MRI-guided cardiac-induced target motion tracking for atrial fibrillation cardiac radioablation. (November 2021) - Lydiard, Suzanne; Pontré, Beau; Hindley, Nicholas; Lowe, Boris S; Sasso, Giuseppe; Keall, Paul
Highlights: MRI-guided tracking of atrial fibrillation cardiac radioablation targets. Investigating a cardiac motion compensation technique for cardiac radioablation. Tracking performance in atrial fibrillation and healthy participants was comparable. Results of this study warrant the further investigation of this technique. Abstract: Background and purpose: Atrial fibrillation (AF) cardiac radioablation (CR) challenges radiotherapy tracking: multiple small targets close to organs-at-risk undergo rapid differential cardiac contraction and respiratory motion. MR-guidance offers a real-time target tracking solution. This work develops and investigates MRI-guided tracking of AF CR targets with cardiac-induced motion. Materials and methods: A direct tracking method (Trackingdirect ) and two indirect tracking methods leveraging population-based surrogacy relationships with the left atria (Trackingindirect_LA ) or other target (Trackingindirect_target ) were developed. Tracking performance was evaluated using transverse ECG-gated breathhold MRI images from 15 healthy and 10 AF participants. Geometric and volumetric tracking errors were calculated, defined as the difference between the ground-truth and tracked target centroids and volumes respectively. Transverse, breath-hold, noncardiac-gated cine images were acquired at 4 Hz in 5 healthy and 5 AF participants to qualitatively characterize tracking performance on images more comparable to MRILinac acquisitions. Results: The average 3D geometric tracking errors for Trackingdirect, Trackingindirect_LA and Trackingindirect_target respectively were 1.7 ± 1.2 mm, 1.6 ± 1.1 mm and 1.9 ± 1.3 mm in healthy participants and 1.7 ± 1.3 mm, 1.5 ± 1.0 mm and 1.7 ± 1.2 mm in AF participants. For Trackingdirect, 88% of analyzed images had 3D geometric tracking errors <3 mm and the average volume tracking error was 1.7 ± 1.3 cc. For Trackingdirect on non-cardiac-gated cine images, tracked targets overlapped organsat-risk or completely missed the target area on 2.2% and 0.08% of the images respectively. Conclusion: The feasibility of non-invasive MRI-guided tracking of cardiac-induced AF CR target motion was demonstrated for the first time, showing potential for improving AF CR treatment efficacy.